Pelatihan Pidato Da’I Cilik Dalam Kegiatan Festival Anak Soleh di Desa Telaga Said Kecamatan Sei Lepan Kabupaten Langkat - Muhammad Arfan Harahap; Azhar; Wahyu Pratama; Nafra Andhira; Tiur Ayuningtias Pauliza Lubis; Putri Rahayu (peduli riset dan pengabdian masyarakat, 2023)
Community service is one of the pilars of the tri dharma of higher education . One form its realizition is through cooperation between the regional govement and universities in the formation of KKN which is sustainable and provides mutual benefit , symbosis of loadelism . The purpose of this PKM is to improve the moral competence and etiquette of elementary school age children in Telaga Said village through the implementation of an activity program entitled “ Sholeh Children Festival “ FAS ) held by KKN student rom Stai - Jm Tanjung Pura who are directly guided by field supervisiors ( DPL ) One of The competitions in the fas is the Preachers speech . Through this Litlle Preacher’s speech training , it is hoped that it will be able to create generations of faith , Piety good morals and good character with the aim of getting used to speaking in public and interested in exploring the material to be conveyed